Comparative study of 25 µg vaginal misoprostol v/s cerviprime gel for induction of labour at term - Parmar, Monica; Aherwar, Rupa; Aherwar, Rupa; Jahan, Ishrat; Jahan, Ishrat (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: This comparative study was conducted to compare the effectiveness of 25 µg of intravaginal misoprostol with intracervical cerviprime gel in terms of efficacy of drug, foeto-maternal outcome, side effects and complications of drugs. Methods: 100 primigravida at term; who were admitted for induction of labour were included in this study. They were randomly selected to receive either intravaginal misoprostol or intracervical cerviprime gel. 50 women received intravaginal 25 µg Misoprostol (Group A) every 6 hours for maximum of 5 doses and 50 women received 0.5 mg (2.5 ml) of intracervical cerviprime gel (Group B) till maximum of 3 doses. Comparison was done in terms of time taken for induction to delivery, mean time taken for onset of labour, APGAR score at 1 and 5 minutes and the neonatal outcome in either of the groups. Results: The mean time taken for onset of labour was less in the misoprostol group than in the cerviprime group (6.5 hours v/s 8 hours, P = 0.49). Similarly duration from induction to delivery was less (20.08 ± 8.24 hours v/s 23.19 ± 9.59 hours, P >0.05) for misoprostol than cerviprime gel. Need for Oxytocin augmentation was less (16%) in misoprostol group as compared to cerviprime group (46%), P = 0.001. Cesarean section rate was slightly higher in misoprostol group (8% v/s 6%). Maternal complications were minimal in either group & the neonatal outcome was good in both the groups. The induction cost was much less in the misoprostol group. Conclusions: Compared to cerviprime gel; misoprostol is safe, efficacious, cheap, well tolerated drug by mother and fetus. It was found to be a better inducing agent, has short induction to delivery interval thus short duration of labour with similar maternal and fetal safety profile.